The crowding-out effect of the environmental regulation on corporate sustainability - Yuan, Ke; Wu, Bangzheng (Frontiers in Environmental Science, 2024)
The analysis of the impact of China's Environmental Protection Tax (EPT) Law on company environmental, social, and corporate governance (ESG) performance is crucial for a more comprehensive understanding of the EPT Law and to improve corporate practices. Using a difference-in-differences (DID) model with a research sample of 7,055 listed firms in China from 2012 to 2020, we found that the EPT Law significantly improved firms' overall ESG performance. However, this improvement was mainly driven by significant increases in the environmental (E) score. In contrast, the social (S) score declined significantly after the implementation of the EPT Law, indicating a trade-off between environmental regulation and social responsibility. Further analysis also reveals that the increase in production costs, which led to a decrease in employment and wages, is responsible for the crowding-out of social responsibility. This study not only enhances our understanding of the impacts of environmental regulations on companies but also offers guidelines for policymakers to consider the negative externality of policies, which could serve as a "double edged sword."